The Inquisition outside Baghdad - Melchert, Christopher ca. 20./21. Jh. (Journal of the American Oriental Society, 2021)
The Inquisition (miḥna) of al-Maʾmūn (d. 218/833) was a serious attempt to establish the caliph as arbiter of Islamic orthodoxy. It was actively prosecuted by the succeeding two caliphs, and finally abolished by his nephew, the caliph al-Mutawakkil, in 237/852. The most information we have about it by far is how it was carried out in Baghdad. Various sources, mostly biographical, also tell us something of its prosecution in Basra, Kufa, Damascus, Isfahan, Old Cairo (Fustat), and Qayrawan, surveyed here. These scattered data confirm that it was largely about bringing the emerging scholarly class under control. They may also indicate that the Inquisition was instituted not in 218 but already in 217/832-3.